2010
DOI: 10.1002/hep.23785
|View full text |Cite
|
Sign up to set email alerts
|

Long-term entecavir therapy results in the reversal of fibrosis/cirrhosis and continued histological improvement in patients with chronic hepatitis B

Abstract: One year of treatment with entecavir (0.5 mg daily) in nucleoside-naive patients with hepatitis B e antigen (HBeAg)-positive or HBeAg-negative chronic hepatitis B (CHB) resulted in significantly improved liver histology and virological and biochemical endpoints in comparison with lamivudine. Patients who received at least 3 years of cumulative entecavir therapy in phase 3 studies and a long-term rollover study and underwent long-term liver biopsy were evaluated for improvements in histological appearance. Sixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
656
3
24

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 889 publications
(717 citation statements)
references
References 39 publications
19
656
3
24
Order By: Relevance
“…Long-term viral suppression was found to be associated with histologic improvement in the reduction of fibrosis and ultimately regression of cirrhosis [13]. Furthermore, a study has demonstrated that adult patients with CHB need over 2 years of NUC treatment to reduce risk of cirrhosis, HCC or CHB-related death [14].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term viral suppression was found to be associated with histologic improvement in the reduction of fibrosis and ultimately regression of cirrhosis [13]. Furthermore, a study has demonstrated that adult patients with CHB need over 2 years of NUC treatment to reduce risk of cirrhosis, HCC or CHB-related death [14].…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Histological improvement was observed in 66 of the 69 patients (96%) who had received entecavir for 3 to 7 years. 16 In a randomized trial of 191 patients with decompensated cirrhosis, entecavir-treated patients tended to have lower incidence of HCC than those treated with adefovir at 48 weeks. 17 However, due to the short duration of follow-up, the difference between the two groups was uncertain, and some patients might have already harbored undiagnosed HCC before antiviral therapy.…”
mentioning
confidence: 99%
“…All these factors may elicit significant bias between groups. Use of entecavir is proven to be beneficial for hepatitis B virus patients to reverse fibrosis and cirrhosis 6 ; however, the evidence of reduction in hepatic events and incidence of HCC, as revealed by the current study and previous work, 7 was still flawed with significant bias. Long-term follow-up of controlled studies would be more convincing.…”
Section: Finite Entecavir Therapy Is a Feasible Alternative To Indefimentioning
confidence: 52%
“…In our recent analysis, the specificity of AFP was as high as 99% at a cut-off value of 20 mg/L in patients receiving entecavir. 6 …”
Section: Replymentioning
confidence: 99%